The fat body of termites: Functions and stored materials - Costa-Leonardo, Ana Maria [UNESP]; Laranjo, Lara Teixeira [UNESP]; Janei, Vanelize [UNESP]; Haifig, Ives [UNESP] (Elsevier, 2013)
The functions of the fat body in the different castes of termites, and accumulation of energy reserves, proteins and urates within this organ, are reviewed. The termite fat body is involved in multiple metabolic activities, including recycling of nitrogen. Termite fat body showed three different types of cells: adipocytes, urocytes and mycetocytes, the latter restricted to the species Mastotermes darwiniensis. Adipocytes synthesize and store lipids, glycogen and several proteins. These cells also elaborate important peptides, including some that act in immune processes. Urocytes are responsible for the storage of spherocrystals of urates, which vary quantitatively among the termite castes. The different metabolic functions of the fat body in the several castes and stages of termites are associated with specific adipocyte morphologies. The synthesis and storage of different compounds modify the structure of the fat body; this differentiation is coordinated by hormones involved with molting and reproductive cycles. © 2013 Elsevier Ltd.
Keywords: Adipocytes; Isoptera; Storage proteins; Termite queens; Ultrastructure; Urocytes; fat; hormone; immune system; molt; protein; queen; reproductive cycle; termite; ultrastructure